A Study on Knowledge and Skills of Female Health Workers Regarding Maternal Care Under RCH Programme - Lodhiya K, Kaushik; Pithadiya R, Pradeep; Damor D, Raman; Unadkat V, Sumit; Yadav B, Sudha (National Journal of Community Medicine, 2012)
Background: More than three quarters of the population of our country lives in rural areas. The female health workers at the SC have to take care of all the reproductive health needs of the rural population. Hence the present study was conducted with the objective to assess their knowledge & practices in relation to RCH services. Methods & Materials: This was a cross sectional descriptive study, conducted in rural areas of Jamnagar district. All the HW-Fs of the district were included in the study. Results: Out of 218 HW-Fs, only 71.56% were able to enumerate at least 5 criteria of at-risk mothers. Only 40.37% & 60% HW-Fs performed HB estimation & urine investigation of mothers. Only 27.98% knew at least 5 of the indications for referral of the mother in labour to higher centre. Conclusion: The knowledge & skills of HW-Fs was grossly lacking in many basic health care components. Negligence in essential health care practices was detected.